Impact of Financial Stability of Enterprises on Innovative Development Processes - Akram Mirzaevich Amanov (International Journal on Integrated Education, 2023)
This article shows the importance of the financial stability of enterprises in the conditions of modernization of the economy, the current situation, the influence of the financial stability of enterprises on the processes of innovative development, the role of factors affecting the reduction of the cost of manufactured products in ensuring the financial stability of the enterprise, and the ways of assessing the financial stability of enterprises